Robert B. Parker's Lullaby : Spenser #40 - Atkins, Ace, 1970-; Parker, Robert B., 1932-2010; Mantegna, Joe; Random House Audio Publishing; Recorded Books, LLC. (Prince Frederick, MD : Random House Audio, 2012)
Spenser takes up a seemingly open and closed cold case at the behest of a street-wise 16 year old girl, who believes her mother's murderers went free. As Spenser digs deeper into the mystery, he finds a much more dangerous and complex mystery than he bargained for.
Compact disc.
Title from container.
In container (17 cm.).
Read by Joe Mantegna.
Keywords: Spenser (Fictitious character) -- Fiction; Mothers -- Crimes against -- Fiction; Private investigators -- Massachusetts -- Boston -- Fiction; Boston (Mass.) -- Fiction; Domestic fiction; Mystery fiction; Audiobooks